Stock Market and No‐Dividend Stocks - ATMAZ, ADEM; BASAK, SULEYMAN (Journal of Finance, 2022)
ABSTRACT We develop a stationary model of the aggregate stock market featuring both dividend‐paying and no‐dividend stocks within a familiar, parsimonious consumption‐based equilibrium framework. We find that such a simple feature leads to profound implications supporting several stock market empirical regularities that leading consumption‐based asset pricing models have difficulty reconciling. Namely, the presence of no‐dividend stocks in the stock market leads to a lower correlation between stock market returns and the aggregate consumption growth rate, a nonmonotonic and even negative relation between the stock market risk premium and its volatility, and a downward‐sloping term structure of equity risk premia.